2009
DOI: 10.3844/ajbbsp.2009.153.161
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Down Regulation of Glycolytic Enzymes, Upregulation of Gluconeogenic Enzymes and Potential Hepato-Nephro-Protective Effects Following the Chronic Administration of the Hypoglycemic, Insulinotropic Citrullus colocynthis Pulp Extract

Abstract: Abstract:Background Citrullus colocynthis pulp seedless extract has been demonstrated to have antihyperglycemic and insulinotropic effects. Problem statement: The mechanism(s) underlying the antihyperglycemic and insulinotropic effects have not been investigated to date. Approach: The influence of Citrullus colocynthis pulp extract administered orally was studied in alloxan diabetic white albino rats. Rats were divided into four groups, the first group was normal non diabetic rats given normal saline orally an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Thus, extracts from different parts of this plant may be useful for reducing diabetes complications in the long-term. Moreover, previous studies have shown that the administration of 500 mg/kg of C. colocynthis extract resulted in a significant reduction in blood glucose (17)(18)(19)(20). Also, Dallak et al confirmed that the administration 20 mg/kg fruit extract of C. colocynthis produced a significant reduction in blood glucose (19).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, extracts from different parts of this plant may be useful for reducing diabetes complications in the long-term. Moreover, previous studies have shown that the administration of 500 mg/kg of C. colocynthis extract resulted in a significant reduction in blood glucose (17)(18)(19)(20). Also, Dallak et al confirmed that the administration 20 mg/kg fruit extract of C. colocynthis produced a significant reduction in blood glucose (19).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, previous studies have shown that the administration of 500 mg/kg of C. colocynthis extract resulted in a significant reduction in blood glucose (17)(18)(19)(20). Also, Dallak et al confirmed that the administration 20 mg/kg fruit extract of C. colocynthis produced a significant reduction in blood glucose (19). In a study conducted on alloxan-diabetic rats, the results suggested that oral administration leaf extract of C. colocynthis (250 and 500 mg/kg) leads to a reduction in the serum level of glucose after 8 weeks intervention (17).…”
Section: Discussionmentioning
confidence: 97%
“…Immunohistochemistry procedure showed that the amount of insulin in beta-cells of the islets of Langerhans is greater in Citrullus colocynthis treated-diabetic rats in comparison to the control group [28] . Administration of the ethanol extract of the dried seedless pulp of Citrullus colocynthis at 300 mg/kg, p.o had insulinotropic actions in alloxan-induced diabetic rats [29] . Aqueous extract of Citrullus colocynthis showed dose-dependent increase in insulin release from isolated islets [12] .…”
Section: Citrullus Colocynthis (Cucurbitaceae)mentioning
confidence: 88%
“…Babu et al (2006) have reported that green tea attenuates cardiac dysfunction in DCM. Investigations have revealed improved enzyme homeostasis and end organ function with Citrullus colocynthis (L.) Schrad (Dallak et al, 2009) and protective effect of Embelica ribes Burm (Myrsinaceae) fruit extract in isoproterenol-induced cardiotoxicity in diabetic rats (Bhandari & Ansari, 2009).…”
Section: Research Articlementioning
confidence: 99%